The risk of cervical atypia in oral contraceptive users. (2nd January 2018) - Adhikari, Indira; Eriksson, Tiina; Luostarinen, Tapio; Lehtinen, Matti; Apter, Dan
Abstract: Background: The interactions of oral contraceptive (OC) use, risk of human papillomavirus (HPV) infection and associated cellular atypia are complex. We investigated the association between history of OC-use, and cytological or histopathological abnormalities in a cohort of non-HPV vaccinated originally 16–17-year-old women participating the PATRICIA trial for 4 years. Methods: The total number of hepatitis A-virus (control) vaccine recipients participating in the clinical PATRICIA trial in Finland was 2399. Nine-hundred and ninety-nine women returned questionnaires on living conditions-life habits and sexual health after completing the study. Mean age at answering the questionnaire at the end of the clinical trial was 22 years. Age at sexual debut varied between 12 and 16 years for majority of the women. Cervical cytological samples were obtained every 6 months throughout the PATRICIA trial. The relative risk of cervical atypia associated with time since start of oral contraceptives use was calculated as odds ratio (OR) with 95% confidence interval (CI) using logistic regression. Results: Compared to never-users, the smoking and age-at-sexual-debut adjusted relative risk of cervical intraepithelial neoplasia grade 1 (CIN1) in women who had started the use of oral contraceptives for more than 1 year was low (OR 0.2, 95% CI: 0.1–0.7). Risk of cytological atypia was also reduced (OR 0.6) albeit not significantly (95% CI: 0.3–1.3). Conclusions: Use of oral contraceptives does not increase the risk of cervical atypia but when established might instead be protective.